The Variability of Estimated Glomerular Filtration Rate Decline in Alport Syndrome. Issue 1 (20th December 2016) - Langsford, David; Tang, Mila; Djurdjev, Ognjenka; Er, Lee; Levin, Adeera
Background: A progressive trajectory toward renal failure is common in patients with Alport syndrome. Genotype-phenotype correlations have been well described; however, the natural history of the trajectory toward renal failure is not well described. Objective: The objective of this study is to describe the natural history of renal function decline in a cohort of Alport syndrome patients. Design: Retrospective observational cohort study. Setting: British Columbia, Canada, chronic renal disease registry 1995-2012. Patients: 37 biopsy proven Alport syndrome or hematuria with family history of Alport syndrome. Measurements: Serial estimated glomerular filtration rate (eGFR) Trajectory of renal decline described graphically by fitting a cubic smoothing spline to patient's eGFR measures. Various time points within a trajectory were indexed, randomly sampled, and followed for 2 years to estimate portion of progressors (>5 mL/min/1.73 m2 /y decline), stable state (0-2 mL/min/1.73 m2 /y decline), and regressors (>2 mL/min/1.73 m2 /y incline). Methods: In this retrospective observational cohort study, participants were identified through a chronic renal disease registry in British Columbia, Canada, from 1995 to 2012. Inclusion criteria were biopsy proven or hematuria with a family history of Alport syndrome. Individual patients and family group members were studied. Trajectory of renal decline described graphically by fitting a cubic smoothing spline to patient's serial estimated glomerular filtration rate (eGFR) measures. Various time points within a trajectory were indexed, randomly sampled, and followed for 2 years to estimate portion of progressors (>5 mL/min/1.73 m 2 /y decline), stable state (0-2 mL/min/1.73 m 2 /y decline), and regressors (>2 mL/min/1.73 m 2 /y incline). Limitations: Histological or genetic evidence of Alport syndrome is not available in all patients. Results: Median follow-up time was 48.2 months of 37 patients (78% male), with a median age of 36 (interquartile range [IQR], 18-47) and a median age of renal replacement therapy commencement (n = 23) of 38 (IQR = 20-52). Renal function changes were found to be heterogeneous overall, intra-individual and within families. Portion of progressors in eGFR 45-60 mL/min/1.73 m 2 was 73.7% (SD, 10.3), whereas 23.6% (SD, 11.0) remained stable. Within eGFR 30-45 mL/min/1.73 m 2, 45.6% (SD, 7.0) were progressors, whereas 53.4% (SD, 7.4) remained stable. A large portion of eGFR 15-30 mL/min/1.73 m 2 patients were stable (54.8%; SD, 8.4), whereas 25.7% (SD, 7.1) progressed and 19.5% (SD, 5.6) regressed. Conclusions: The renal decline in Alport syndrome patients is heterogeneous which has implications for designing clinical trials of interventions.